The Effect of Quranic Murotal Therapy on Anxiety Levels in Maternity Women at the Midwife Independent Practice (TPMB) A, Purwakarta Regency, Indonesia - Widiyastuti, Rika (HM Publisher, 2023)
Quranic murotal therapy can also help individuals deepen their spiritual connection and feel a closeness to God. For individuals who experience symptoms of depression, this therapy can help reduce these symptoms and provide positive encouragement. This therapy can help individuals develop feelings of gratitude for life's blessings, which can reduce feelings of dissatisfaction and unhappiness. This study aimed to determine the effect of Quranic murotal therapy on anxiety levels in maternity women at TPMB (Midwife Independent Practice) A, Purwakarta Regency, Indonesia. This study is experimental research with a one-group pre-post test approach. This study uses primary data, namely measuring the degree of anxiety of birth mothers in research respondents. A total of 30 research subjects took part in this study. This study shows that the intervention of providing Quranic murotal is effective in reducing the level of anxiety of mothers giving birth. There was a decrease in the level of anxiety of mothers giving birth after giving Quranic murotal, and it was stated to be statistically different, p<0.05. In conclusion, there is an influence of Quranic murotal therapy on the level of anxiety in maternity women at TPMB (Midwife Independent Practice) A, Purwakarta Regency, Indonesia.